Flexible phase change fiber membrane based on electrostatic spinning process and preparation method and application thereof

The flexible phase-change fiber membrane prepared by electrospinning process combines polyacrylonitrile and phase-change materials to solve the problems of high thermal conductivity and low photo-thermal conversion rate of composite phase-change materials, and achieves efficient photo-thermal conversion and thermal management performance.

CN119711048APending Publication Date: 2025-03-28ZHONGBEI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411941962.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing composite phase change materials have high thermal conductivity and low photothermal conversion rate, making it difficult to achieve good thermal insulation and photothermal energy storage at the same time.

Method used

Flexible phase-changing fiber membranes are prepared by electrospinning process. By mixing polyacrylonitrile (PAN) as a fiber base material with phase-changing material and light-absorbing filler (such as ZIF-based porous carbon material or gelatin-based porous carbon material), a phase-changing composite nanofiber film with thermal insulation and photothermal conversion functions is formed.

Benefits of technology

It realizes efficient photothermal conversion and thermal management performance, improves thermal conductivity and photothermal conversion rate, and is suitable for building insulation materials and clothing insulation layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119711048A_ABST
    Figure CN119711048A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: mixing polyacrylonitrile serving as a fiber substrate material with a phase change material, and adding a ZIF-based porous carbon material or a gelatin-based porous carbon material serving as a light absorption filler; the phase change composite nanofiber film with heat preservation, heat insulation and photo-thermal conversion functions is prepared in an electrostatic spinning mode. The flexible phase change fiber membrane still has good shape stability in a phase change behavior, also has excellent photothermal conversion performance and thermal insulation performance, and can be applied as a building thermal insulation material and a clothing thermal insulation layer material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photothermal energy storage materials, and relates to a composite nanofiber membrane material with photothermal conversion and thermal management performance. Background Art

[0002] Building energy consumption refers to the temperature regulation of buildings during their use, and the consumption of energy through conduction, convection and radiation, which accounts for a large proportion of the world's energy consumption today.

[0003] Thermal insulation of buildings is an important parameter for reducing building energy consumption. Rock wool and glass wool are currently the most commonly used thermal insulation materials, with thermal conductivity coefficients up to 0.046W / m·K. Although their thermal insulation performance is good, pure thermal insulation materials lack heat storage function and comfort needs to be improved.

[0004] The application of phase change materials in building materials is considered an effective means to reduce energy consumption and improve comfort. Phase change materials have high latent heat. When the ambient temperature is higher than the phase change temperature, they absorb heat and store it in the phase change material. When the temperature drops to the phase change temperature, the heat is released into the environment to maintain a relatively constant temperature. Studies have found that the combination of thermal insulation materials and phase change materials can achieve better results. The use of thermal insulation phase change materials in building walls can greatly maintain the indoor temperature at a more comfortable level.

[0005] Cabeza et al. (Experimental study on the performance of insulation materials in Mediterranean construction. Energy and Buildings , 2010, 42:5.10.) Insulating materials such as polyurethane have been added to the building envelope in cold winter regions. The results show that this design significantly reduces the building's energy consumption in winter, especially during peak loads.

[0006] Another study by Kosny et al. (Field thermal performance of naturally ventilated solar roof with PCM heat sink. Solar Energy , 2012, 86: 9.) discusses field thermal performance data of an experimental PV-PCM roof / attic system by adding a phase change material heat sink to the roof design. By comparing it to an asphalt shingle roof, it is shown that the experimental roof configuration can reduce heating loads by approximately 30% and cooling loads by 50%.

[0007] Jaynul Abden et al. (Combined use of phase change material and thermalinsulation to improve energy efficiency of residential buildings. Journal of Energy Storage , 2022, 56(PA).) developed a composite shape-stable phase change material FSPCM, which uses methyl stearate as the phase change material and diatomaceous earth as the packaging material, and found that diatomaceous earth can improve the thermal conductivity of PCM and prevent potential leakage. However, the effect of this study in cold regions is not obvious.

[0008] Although the above studies have further verified the potential of phase change materials in building energy conservation, the current research on phase change materials based on the combination of thermal insulation and light-heat conversion is relatively shallow. Therefore, the composite material technology combining thermal insulation materials and phase change materials has become a cutting-edge trend in the field of architectural design, especially in reducing building energy consumption, improving energy efficiency, and improving indoor comfort, showing significant advantages. Summary of the invention

[0009] The purpose of the present invention is to provide a flexible phase change fiber membrane based on an electrospinning process and a preparation method thereof, so as to solve the problems of high thermal conductivity and low light-to-heat conversion rate of current composite phase change materials.

[0010] The flexible phase change fiber membrane based on the electrospinning process described in the present invention is a phase change composite nanofiber film with thermal insulation and light-to-heat conversion functions prepared by electrospinning, using polyacrylonitrile (PAN) as the fiber base material, mixed with a phase change material and added with a light-absorbing filler.

[0011] Wherein, the light-absorbing filler is a ZIF-based porous carbon material or a gelatin-based porous carbon material.

[0012] More specifically, the ZIF-based porous carbon material may be carbonized ZIF-67 (GC) or carbonized ZIF-8.

[0013] The phase change material may be any conventional organic phase change material, including but not limited to polyethylene glycol or n-octadecane.

[0014] Furthermore, in the phase-change composite nanofiber film of the present invention, the mass ratio of the phase-change material, the light-absorbing filler and the fiber base material is preferably 11:1-2.5:5-11.

[0015] The present invention also provides a method for preparing the flexible phase change fiber membrane, which specifically comprises: 1) dispersing the light-absorbing filler in a good solvent of the polyacrylonitrile fiber base material, adding a phase change material to dissolve evenly, and then adding the polyacrylonitrile fiber base material to dissolve evenly to form an electrospinning solution; 2) using an electrospinning process, the electrospinning solution is sprayed onto a collecting drum under the action of an electrostatic force of an electric field formed by a high voltage to form a nanofiber membrane; 3) Collecting the nanofiber membrane and obtaining a shape-stable phase-change composite nanofiber membrane after solidification.

[0016] Among them, the present invention preferably disperses the light-absorbing filler in a good solvent of polyacrylonitrile and performs ultrasonic treatment to make it dispersed evenly.

[0017] Furthermore, the present invention further performs ultrasonic crushing treatment on the light absorbing filler based on the ultrasonic treatment.

[0018] Preferably, the present invention is to stir the electrospinning solution at high speed overnight to further form a uniform electrospinning solution.

[0019] More specifically, the good solvent of the polyacrylonitrile fiber base material may include but is not limited to N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), acetone or methylpyrrolidone. In the present invention, DMF is preferably used.

[0020] The electrospinning process used in the present invention is a conventional mature process method. Preferably, the present invention specifically sets the spinning voltage in the electrospinning process to be 13-16.5 kV, and the electrospinning solution feeding speed to be 0.5-2 mL / h.

[0021] Furthermore, in the electrostatic method process of the present invention, the preferred electrospinning solution spraying distance, that is, the distance between the electrospinning solution nozzle and the collecting drum is 15 to 20 cm.

[0022] Furthermore, the rotation speed of the collecting drum in the electrospinning process is preferably 300 rpm.

[0023] Furthermore, the present invention preferably keeps the collected nanofiber membrane at 40-60° C. for not less than 12 hours to fully solidify it to obtain a shape-stable phase-change composite nanofiber membrane.

[0024] The present invention utilizes the good compatibility of phase change materials such as PEG and PAN in their good solvents. After sufficient ultrasonic dispersion and ultrasonic crushing treatment, the phase change material is compounded with a light-absorbing filler with low cost and excellent absorbance in a nanofiber network with PAN as the fiber base, and a thermal insulation composite nanofiber film with excellent heat storage capacity is successfully constructed. After testing, it is found that it not only has excellent light-to-heat conversion ability, but also has good thermal insulation and heat energy storage performance.

[0025] The use of light-absorbing fillers in the present invention, on the one hand, is based on its low cost, which reduces the economic pressure for the large-area use of phase-change composite nanofiber membranes. On the other hand, the light-absorbing fillers not only have good photothermal conversion performance, but also their addition can significantly reduce the viscosity of the electrospinning solution, thereby allowing PEG to be more evenly dispersed in the PAN fibers.

[0026] The phase-change composite nanofiber membrane prepared by the present invention has broad application prospects in photothermal energy storage, thermal insulation and wearable devices, and can be used as a building thermal insulation material and a clothing insulation layer material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 These are SEM images of GC prepared in Example 1 at different magnifications.

[0028] Figure 2 This is the XRD pattern of GC prepared in Example 1.

[0029] Figure 3 It is the FTIR spectrum of different fiber membranes.

[0030] Figure 4 It is the XRD image analysis diagram of different fiber membranes.

[0031] Figure 5 are scanning electron micrographs of different fiber membranes.

[0032] Figure 6 It is the energy dispersion spectrum of different fiber membranes.

[0033] Figure 7 These are the TG and DSC graphs of different fiber membranes.

[0034] Figure 8 These are the flexibility test results of different fiber membranes.

[0035] Fig. 9 These are the leakage rate test results of different fiber membranes.

[0036] Fig.10 It is the infrared thermal imaging and thermal conductivity curve of different fiber membranes.

[0037] Fig.11It is a graph showing the absorbance of different fiber membranes and the temperature change trend with illumination time.

[0038] Fig.12 This is a test chart of thermal insulation performance of different fiber membranes. Implementation

[0039] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.

[0040] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.

[0041] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example

[0042] Example 1

[0043] 4.658 g of cobalt nitrate hexahydrate was added to 80 mL of methanol and stirred for 30 min to obtain a cobalt salt solution.

[0044] Weigh 10.508 g of 2-methylimidazole, mix and dissolve it in 80 mL of methanol for 30 minutes to obtain a 2-methylimidazole solution.

[0045] The two solutions were mixed under magnetic stirring for 16 hours, and the synthesized purple solution was centrifuged at 10,000 rpm for 5 minutes, rinsed with methanol for several times, and air-dried at 60° C. for 8 hours to prepare the metal organic framework material ZIF-67.

[0046] The product was ground, heated to 800°C at a rate of 2°C / min and carbonized for 2h. After cooling, it was ground to obtain carbonized ZIF-67, which was recorded as GC.

[0047] Figure 1SEM images of GC at different magnifications are provided, and it can be seen that GC is a sheet-like structure. From the macroscopic observation of (d), GC is a block-like substance. Further, (c) shows that there are particles on the surface of the object, and (b) observes that the GC surface has a fibrous structure. Finally, in (a), it can be seen that there are irregular protrusions and depressions on the surface of GC. Its unique structure is easy to stack during the spinning process, which greatly limits the formation of the heat conduction path of the fiber membrane, thereby presenting a better thermal insulation effect.

[0048] Figure 2 In the XRD diagram of GC, the diffraction peak at 2θ=26° corresponds to the (002) crystal plane of graphite carbon sheet (PDF#15-0806), while the diffraction peaks at 2θ=44.3°, 51.6° and 75.8° are characteristic diffraction peaks of elemental cobalt (PDF#99-0057), indicating that the cobalt in GC exists in elemental form and GC is successfully prepared.

[0049] Example 2

[0050] Weigh 0.5984 g of GC in 25 mL of DMF, treat it with an ultrasonic cleaner at a power of 350 W for 1 h to fully disperse GC in DMF, then put it into an ultrasonic cell disruptor and ultrasonically disrupt it at a power of 120 W for 1.5 h to obtain a GC suspension with good dispersion.

[0051] 3.125 g of PEG-6000 was added to the GC suspension, and stirred at 600 rpm in a 60°C water bath for 30 min until completely dissolved. Then 2.5 g of PAN powder was added, and stirred at 1200 rpm at 60°C overnight to form a viscous polymer solution for electrospinning.

[0052] In the electrospinning polymer solution, the mass percentages of GC, PEG-6000, PAN and solvent DMF are 2.0wt%, 10.4wt%, 8.3wt% and 79.3wt% respectively.

[0053] The distance between the polymer solution nozzle of the electrospinning device and the cylindrical aluminum foil collector was set to 18 cm, and the rotation speed of the cylindrical aluminum foil collector was 300 rpm. The polymer solution for electrospinning was transferred into a liquid storage tube, and pushed to the nozzle through a hose at a liquid inlet rate of 1.5 mL / h under the push of a propulsion pump. Under the action of the electrostatic force of the electric field formed by the 15 kV high voltage, the polymer solution was ejected from the nozzle and stretched into fibers, which were evenly distributed on the cylindrical aluminum foil collector to form a nanofiber membrane.

[0054] The nanofiber membrane was collected, placed in a vacuum drying oven, and kept at 60°C for 12 h to completely solidify it, thereby preparing a shape-stable phase-change composite nanofiber membrane, which was recorded as GC@PEG / PAN-2.

[0055] Example 3

[0056] Weigh 0.296 g of GC in 25 mL of DMF, treat it with an ultrasonic cleaner at a power of 350 W for 1 h to fully disperse GC in DMF, then put it into an ultrasonic cell disruptor and ultrasonically disrupt it at a power of 120 W for 1 h to obtain a GC suspension with good dispersion.

[0057] 3.125 g of PEG-6000 was added to the GC suspension, and stirred at 600 rpm in a 60°C water bath for 30 min until completely dissolved. Then 2.5 g of PAN powder was added, and stirred at 1200 rpm at 60°C overnight to form a viscous polymer solution for electrospinning.

[0058] In the electrospinning polymer solution, the mass percentages of GC, PEG-6000, PAN and solvent DMF are 1.0 wt %, 10.6 wt %, 8.4 wt % and 80.0 wt % respectively.

[0059] Using the above-mentioned electrospinning polymer solution, according to the electrospinning method in Example 2, a shape-stable phase-change composite nanofiber membrane was prepared, which was recorded as GC@PEG / PAN-1.

[0060] Example 4

[0061] The PEG-6000 in Example 2 was replaced by 3.125 g of n-octadecane. The other aspects were the same as in Example 2. The phase change composite nanofiber membrane n-octadecane / PAN / GC was prepared according to the method in Example 2.

[0062] Example 5

[0063] The GC in Example 2 was replaced by 0.5984 g of carbonized ZIF-8. The other conditions were the same as those in Example 2. The phase change composite nanofiber membrane PEG / PAN / carbonized ZIF-8 was prepared according to the method in Example 2.

[0064] Example 6

[0065] The GC in Example 2 was replaced by 0.5984 g of carbonized gelatin, and the PEG-6000 in Example 2 was replaced by 3.125 g of n-octadecane. The other conditions were the same as those in Example 2. The phase change composite nanofiber membrane n-octadecane / PAN / carbonized gelatin was prepared according to the method in Example 2.

[0066] Comparative Example

[0067] 3.125 g of PEG-6000 was weighed into 25 mL of DMF and stirred at 600 rpm in a 60°C water bath for 30 min until completely dissolved. Then 2.5 g of PAN powder was added and stirred at 1200 rpm at 60°C overnight to form a viscous polymer solution for electrospinning.

[0068] The distance between the polymer solution nozzle of the electrospinning device and the cylindrical aluminum foil collector was set to 18 cm, and the rotation speed of the cylindrical aluminum foil collector was 300 rpm. The polymer solution for electrospinning was transferred into a liquid storage tube, and pushed to the nozzle through a hose at a liquid inlet rate of 1.5 mL / h under the push of a propulsion pump. Under the action of the electrostatic force of the electric field formed by the 15 kV high voltage, the polymer solution was ejected from the nozzle and stretched into fibers, which were evenly distributed on the cylindrical aluminum foil collector to form a nanofiber membrane, which was placed in a vacuum drying oven and kept at 60°C for 12 hours to completely solidify, and a shape-stable phase-change composite nanofiber membrane was obtained, which was recorded as PEG / PAN.

[0069] Application Example 1

[0070] The relevant properties of the fiber material PAN, the phase change material PEG, the light-absorbing filler GC, and the phase change composite nanofiber membranes GC@PEG / PAN-2, GC@PEG / PAN-1 and PEG / PAN prepared in Example 2, Example 3 and the comparative example were characterized.

[0071] Figure 3 In the FTIR spectrum of PEG, the peak at 1377 cm -1 and 2930cm -1 The absorption peak at 1152 cm -1 There is an obvious absorption band at 1493 cm, which is due to the stretching vibration of the COC group. The characteristic absorption peak of PAN absorption spectrum is located at 1493 cm -1 and 2288cm -1 , corresponding to the torsional vibration of the -CH2- group and the stretching vibration of C≡N respectively; while GC is obtained by high-temperature decomposition of ZIF-67 at 800℃, and its functional groups have been completely decomposed, and no obvious characteristic peaks can be observed in the FTIR spectrum.

[0072] Depend on Figure 3 It can be seen that the characteristic peaks of the three fiber membranes are simply superimposed by the characteristic peaks of PEG and PAN, and no new characteristic peaks are involved, which also shows that the introduction of GC does not involve chemical reactions.

[0073] Figure 4In the X-ray diffraction (XRD) diagram, the characteristic peaks of PEG are located at 19.0° and 23.6°, corresponding to planes (120) and (032), respectively; the characteristic peak of PAN is located at 17.3°, corresponding to plane (100); and the above characteristic peaks exist in all three fiber membranes. The peak 2θ=26° of GC corresponds to the crystal plane (002) of graphite carbon sheets, while the diffraction peaks at 2θ=44.3°, 51.6° and 75.8° are the diffraction peaks of elemental cobalt, indicating that cobalt in GC exists in elemental form. In addition to the PEG / PAN fiber membrane, its characteristic peaks also appear in the other two fiber membranes.

[0074] The above XRD and FTIR results prove that the characteristic peaks of PEG are present in the three fiber membranes with different contents, indicating that the electrospinning method can successfully encapsulate PEG. Based on the fact that the diffraction peaks of the fiber membrane are simply superpositions of the diffraction peaks of each component and no new peaks appear, it shows that GC is successfully compounded in the fiber membrane by physical means without involving chemical reactions.

[0075] Application Example 2

[0076] SEM test was further conducted on the microscopic morphology characteristics of the phase change composite nanofiber membranes GC@PEG / PAN-2, GC@PEG / PAN-1 and PEG / PAN prepared in Example 2, Example 3 and the comparative example. The results are as follows: Figure 5 shown.

[0077] The fiber surfaces of various phase-change composite nanofiber membranes at different magnifications in the figure are relatively smooth, which can be attributed to the good intermolecular forces between PEG and PAN in DMF. Figure 1 The GC is shown in the figure as a flake structure, but during the preparation of the electrospinning solution, the GC was ultrasonically broken and dispersed, and the aggregates were dispersed into small particles, which could be dispersed more evenly on the PAN fibers.

[0078] Furthermore, by Figure 5 From (a~a'') in the figure, it can be seen that the surface of PEG / PAN fiber has irregular protrusions. This is because the PEG content is too high and cannot be evenly dispersed on PAN. The addition of GC in the present invention is beneficial to the dispersion of PEG. Figure 5 From the morphology of GC@PEG / PAN-1 (b~b'') and GC@PEG / PAN-2 (c~c''), it can be clearly seen that as the GC content increases, the fiber diameter of the fiber membrane gradually decreases. This is because the fiber diameter will shorten as the viscosity of the spinning solution decreases. The addition of GC is beneficial to reduce the viscosity of the spinning solution and promote the dispersion of PEG in PAN. At the same time, when the mass of GC reaches 2% of the spinning solution, the viscosity of the spinning solution decreases to a certain extent, and the surface tension of the ejected droplets is not enough to balance the electric field force and gravity, resulting in more large droplets on the fiber membrane.

[0079] By observing the element distribution in different nanofiber membranes, e.g. Figure 6 As shown, it can be further proved that elements such as Co are successfully distributed on the surface of the fiber membrane, and further proved that GC is successfully incorporated into the PEG / PAN fiber membrane (a is GC@PEG / PAN-1, b is GC@PEG / PAN-2).

[0080] Application Example 3

[0081] The thermal stability of each fiber membrane can be characterized by TGA curve. Figure 7 As shown in (a), PEG decomposes rapidly at around 400°C, and loses more than 99.9% of its mass at around 440°C, with the remainder likely to be impurities.

[0082] The thermal decomposition curves of the three nanofiber membranes can be roughly divided into two stages, 280-400℃ and 400-440℃. The first stage is due to the thermal decomposition of PAN (PAN begins to partially decompose at around 280℃, the nitrile group breaks and reorganizes, and finally exists in the form of carbon), which leads to the mass loss of the fiber membrane; the second stage is mainly the thermal decomposition of PAN and PEG. Among the three fiber membranes, PEG / PAN without GC added has the largest mass loss at 800℃, reaching more than 78%. After adding GC, since PEG is adsorbed on the pores and outer surface of GC, the final mass loss of the fiber membrane is only about 65%, proving that the fiber membrane after adding GC shows better thermal stability under the same conditions.

[0083] Differential scanning calorimetry was used to characterize the performance of the three fiber membranes. The test was carried out in a nitrogen environment and heated from room temperature to 200°C at a heating rate of 4°C / min. The DSC curves of the fiber membranes are shown in Figure 7 As shown in (b), the PEG / PAN fiber membrane has the highest enthalpy value, reaching 86.62 J / g, and the GC@PEG / PAN-2 fiber membrane has the lowest enthalpy value, only 74.51 J / g. This is mainly due to the change in the content of PEG in the fiber membrane. The addition of GC reduces the relative content of PEG in the fiber membrane, and the enthalpy value of the fiber membrane decreases to varying degrees.

[0084] in addition, Figure 8 The flexibility test process of the fiber membrane is given. It can be seen that the three fiber membranes have good flexibility. Under the action of external force, they can be bent 180° relatively easily and return to their original shape after the external force disappears.

[0085] Fig. 9The leakage rate test results of the fiber membrane are shown in Figure 2. The three fiber membranes were placed in ovens at 20℃, 40℃, 60℃ and 80℃ respectively. After 1 hour, there was no leakage on the surface of the three fiber membranes. However, after PEG was placed in an oven at 80℃ for 1 hour, most of the PEG had leaked. The above results show that the electrospinning process and the fiber matrix work together to give the fiber membrane good flexibility and inhibit the leakage of PEG, providing favorable conditions for the practical application of the fiber membrane.

[0086] Application Example 4

[0087] A fiber membrane of 1 cm × 1 cm × 0.8 mm was placed on a heating plate, and the heating plate was heated from 20°C to 100°C. The surface temperature of the fiber membrane and the temperature change of the heating plate were recorded with a handheld infrared camera. The results are shown in Figure 2. Fig.10 (a) in the figure.

[0088] As the temperature of the heating plate increases rapidly, the temperature of the three fiber membranes also increases, as evidenced by the significant changes in the color of the infrared thermal imaging images. Finally, the fiber membranes PAN / PEG, GC@PAN / PEG-1, and GC@PAN / PEG-2 fluctuate at 88, 78.1, and 72.6°C, respectively. Due to the presence of PEG, after the heating plate transfers heat to the fiber membrane, the phase change material absorbs a large amount of heat, which directly causes the equilibrium temperature of the three fiber membranes to be much lower than the temperature of the heating plate.

[0089] Fig.10 As shown in (b), the thermal conductivity of PEG / PAN, GC@PEG / PAN-1 and GC@PEG / PAN-2 are 0.044, 0.047 and 0.052 W / m·K, respectively, which are 13.54%, 14.46% and 16% of the thermal conductivity of pure PEG, respectively. Due to the electrospinning and the presence of a large amount of fiber matrix, the fiber membrane is soft and fluffy, with excellent flexibility, and it becomes extremely difficult to form an interconnected heat transfer path, resulting in an extremely low thermal conductivity of the fiber membrane. With the addition of GC, the thermal conductivity of the fiber membrane increased slightly. However, due to the extremely low thermal conductivity of the fiber membrane, it is difficult to transfer heat in the fiber membrane, and it is very easy to have uneven heat. The drastic fluctuations of the equilibrium temperature in infrared thermal imaging illustrate this point. And due to the presence of phase change materials, the fiber membrane can absorb heat when it is higher than the phase change temperature, and release heat to the surroundings when it is lower than the phase change temperature to maintain temperature stability.

[0090] Application Example 5

[0091] The photothermal conversion performance of the flexible phase change fiber membrane mainly depends on its ability to absorb light. This application example measures the absorbance of the flexible phase change fiber membrane in the UV / visible light range of 200 to 800 nm, proving that the fiber membrane containing only PEG and PAN has limited photothermal conversion capacity. The introduction of GC with strong photothermal conversion capacity can enhance the photothermal conversion capacity of the fiber membrane.

[0092] according to Fig.11 In the method shown in (a), the fiber membrane is placed in a light-proof and sealed box and heated at 130 mW / cm 2 Incandescent lamps are used to simulate sunlight, and thermocouples are installed on the surface of the fiber membrane to transmit the temperature changes of the fiber membrane to the data collection module and output the data through a computer.

[0093] Fig.11 (b) is the absorbance capacity test of the three fiber membranes. From the test results, it can be seen that the addition of GC can significantly improve the absorbance capacity of the fiber membrane.

[0094] Fig.11 (c) The photothermal conversion capability of the fiber membrane was further tested, and it can be observed that the temperature of the three fiber membranes increased rapidly under light irradiation.

[0095] Among them, the temperature rise curve of the fiber membrane PEG / PAN can be roughly divided into three stages. The first stage is roughly from 0s to 500s. In this stage, the temperature rises rapidly at the beginning. In the later stage, as the temperature difference between the fiber membrane and the air becomes larger, the heat dissipation is further enhanced, and the temperature rise rate of the fiber membrane slows down. The second stage is about 500s to 750s. In this stage, the temperature of the fiber membrane remains basically unchanged because the fiber membrane undergoes phase change to absorb the surrounding heat, so the temperature remains basically unchanged. The third stage is roughly from 750s to 3200s. In this stage, the phase change of the fiber membrane is basically completed, and the heat that continues to be absorbed is mainly used to increase its own temperature, eventually reaching about 70°C.

[0096] With the addition of GC in the fiber membrane, its photothermal conversion capacity also increases. The fiber membrane with the highest GC content, GC@PAN / PEG-2, can reach about 83°C at 3200s, which is 13°C higher than PEG / PAN.

[0097] The temperature rise curves of the two fiber membranes with GC added can also be roughly divided into three stages. The first stage is roughly from 0s to 500s. In this stage, the temperature of the fiber membrane rises rapidly, with a rising rate of about 0.15℃ / s, while PEG / PAN is only 0.09℃ / s. Its rising rate is greater than PEG / PAN, which can be attributed to the strong light-to-heat conversion ability of GC. The second stage is roughly from 500s to 750s. The reason why the temperature of the fiber membrane drops in this stage may be that GC has good thermal insulation performance. After the absorbed light energy is converted into thermal energy, the heat accumulates inside GC instead of being transferred to PEG in time, so it is manifested as a rapid rise in the temperature of the fiber membrane, which is shown as no phase change process in the figure; after a period of time, PEG undergoes a phase change at the phase change temperature, and the temperature difference with GC is further expanded. Heat is transferred from GC to the surrounding PEG, and a phase change occurs to quickly absorb the surrounding heat, resulting in a drop in temperature. The third stage is roughly from 750s to 3200s. In this stage, the phase change process is basically completed, and the absorbed heat is mainly used to increase the temperature of the fiber membrane. However, due to the large temperature difference between the fiber membrane temperature and the air temperature, the heat dissipation is fast, and the temperature rise rate of the fiber membrane slows down. Finally, the temperature of GC@PEG / PAN-2 and GC@PEG / PAN-1 reached 83℃ and 78℃ respectively after 3200s, but PEG / PAN was only less than 70℃.

[0098] The photothermal conversion efficiency of the fiber membrane was calculated according to the following formula:

[0099] in: m is the mass of the fiber membrane sample, ΔH is the DSC enthalpy value of the sample, Δt is the illumination time, S is the area of ​​the illuminated sample, C is the specific heat of the sample (the specific heats of PEG / PAN, GC@PEG / PAN-1 and GC@PEG / PAN-2 are 0.2198, 0.2324 and 0.1898 MJ / m 3 K), t is the final temperature of the sample, t 0 is the initial temperature of the sample, E To simulate the light power.

[0100] Finally, the photothermal conversion efficiencies of the three fiber membranes were calculated to be 0.5379%, 0.6242%, and 0.7467%, respectively. The photothermal conversion experiment showed that GC has good light absorption capacity, and the introduction of the fiber membrane can improve the photothermal conversion performance of the fiber membrane.

[0101] Application Example 6

[0102] This application example investigates the thermal insulation and heat preservation properties of the flexible phase change fiber membrane.

[0103] according to Fig.12 In the method shown in (a), a heating plate with specifications of (50°C, 6V) is taken and its five sides are tightly wrapped with thermal insulation foam, leaving only one side with a size of 2×1 cm for placing the test sample, which is recorded as the test side.

[0104] A thermocouple is attached to the test surface and exposed to the air. A 6V voltage is applied to both ends of the heating plate to increase the temperature of the heating plate. The temperature data detected by the thermocouple is collected and recorded by a computer.

[0105] After the test is completed and cooled to room temperature, the flexible phase change fiber membranes (2×1×0.3 cm) prepared in Example 1, Example 2 and Comparative Example 1 are placed on the test surface in turn, and a thermocouple is installed on the outer surface of the fiber membrane. A 6V voltage is loaded at both ends of the heating plate to increase the temperature of the heating plate. The temperature data detected by the thermocouple is collected and recorded by a computer.

[0106] Test results such as Fig.12 As shown in (b), the temperature of the exposed heating plate rises rapidly, and after 1200s, the surface temperature of the heating plate has reached about 45°C. After the three flexible phase change fiber membranes are wrapped on the surface of the heating plate, the surface temperature of the fiber membranes only reaches about 35°C at 1200s, which is much lower than the temperature of the heating plate at the same time, indicating that the fiber membrane has a good thermal insulation effect, and the thermal insulation performance of the three fiber membranes is not much different.

[0107] Take a heating plate of specification (80℃, 12V), wrap its five sides tightly with thermal insulation foam, leaving only one side of size 2×1cm for placing the test sample, recorded as the test side, and install a thermocouple on the test side.

[0108] No fiber membrane was placed on the test surface, and the flexible phase change fiber membranes (2×1×0.3 cm) prepared in Example 1, Example 2 and Comparative Example 1 were placed on the test surface. A voltage of 12 V was loaded at both ends of the heating plate to increase the temperature of the heating plate. The temperature data detected by the thermocouple was collected and recorded by a computer.

[0109] Test results such as Fig.12 As shown in (c), it can be clearly observed that the temperature of the heating plate without fiber membrane on the surface rises slowly, and the temperature reaches about 85°C after 1000s. After the fiber membrane is placed on the surface of the heating plate, the temperature can reach 100°C at 1000s, which is much higher than the temperature of the bare heating plate at the same time, indicating that the fiber membrane has good thermal insulation performance, and the thermal insulation performance of the three fiber membranes is not much different.

[0110] The above test results not only prove that the flexible phase change fiber membrane has good thermal insulation properties and can be used for building thermal insulation materials and clothing insulation layers, but also prove that the addition of GC has little effect on the thermal insulation properties of the fiber membrane.

[0111] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.

Claims

1. A flexible phase change fiber membrane based on electrospinning technology, which is a phase change composite nanofiber film prepared by electrospinning, using polyacrylonitrile as the fiber base material, mixed with a phase change material and adding a light-absorbing filler, wherein the light-absorbing filler is a ZIF-based porous carbon material or a gelatin-based porous carbon material.

2. The flexible phase change fiber membrane according to claim 1, characterized in that The ZIF-based porous carbon material is carbonized ZIF-67 or carbonized ZIF-8.

3. The flexible phase change fiber membrane according to claim 1, characterized in that The phase change material is polyethylene glycol or n-octadecane.

4. The flexible phase change fiber membrane according to claim 1, characterized in that The mass ratio of the phase change material, the light absorbing filler and the fiber base material is 11:1-2.5:5-11.

5. The method for preparing the flexible phase change fiber membrane according to claim 1, comprising: 1) dispersing the light-absorbing filler in a good solvent of the polyacrylonitrile fiber base material, adding a phase change material to dissolve evenly, and then adding the polyacrylonitrile fiber base material to dissolve evenly to form an electrospinning solution; 2) using an electrospinning process, the electrospinning solution is sprayed onto a collecting drum under the action of an electrostatic force of an electric field formed by a high voltage to form a nanofiber membrane; 3) Collecting the nanofiber membrane and obtaining a shape-stable phase-change composite nanofiber membrane after solidification.

6. The preparation method according to claim 5, characterized in that The method also includes dispersing the light absorbing filler in a good solvent of polyacrylonitrile, and performing ultrasonic treatment and ultrasonic crushing treatment.

7. The preparation method according to claim 5, characterized in that The electrospinning voltage was set to 13-16.5 kV.

8. The preparation method according to claim 5, characterized in that The electrospinning solution feed rate is 0.5-2 mL / h.

9. The preparation method according to claim 5, characterized in that The spray distance of the electrospinning solution is 15-20 cm, and the collection drum rotates at 300 rpm.

10. Use of the flexible phase change fiber membrane according to claim 1 as a building thermal insulation material.

Citation Information

Patent Citations

  • Flame-retarding functionalized phase-change composite material

    CN107163590A

  • Photo-thermal composite with light absorption and heating and heat storage functions and preparation method thereof

    CN109609100A

  • Multifunctional flexible phase-change material, preparation method thereof and building material

    CN109705816A

  • Flexible composite phase change film capable of storing heat by using solar energy

    CN117261381A

  • Preparation method of phase change energy storage polymer, phase change energy storage polymer, preparation method of fiber and fiber

    CN117866333A